KARAKTERISTIK DAN ASPEK BIOLOGI Scaphopoda (MOLUSKA) - Putri Sapira Ibrahim (Pusat Penelitian Oseanografi LIPI, 2019)
CHARACTERISTICS AND BIOLOGICAL ASPECTS OF Scaphopoda (MOLLUSCS). Scaphopoda are bilaterally symmetrical marine molluscs, commonly known as the